Laktasi Perspektif Al-Qur’an - Lailatul Istiqomah (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
One of the provisions of the Shari'a described in the Qur'an is regarding lactation or radha'ah (breastfeeding a baby). The word radha'ah in the Qur'an is used for two senses, namely first as one of the reasons for the prohibition of marriage due to siblings (QS. an-Nisa' [4]: 23), and second as a breastfeeding activity for mothers to their babies, where breast milk becomes the main food for babies, especially the first six months of birth, and is highly recommended to be given until the baby is two years old (QS. al-Baqarah [2]: 233). Lactation is the entire process of breastfeeding from the time the milk is produced until the baby sucks and swallows it. Islam has taught every mother to meet the nutritional needs of her baby by breastfeeding for two full years. Breastfeeding the baby will provide many benefits to the baby and mother from various aspects. Among them can protect the baby from various diseases and can speed up the recovery process of the uterus for the mother. However, along with the development of the times that provide everything instantly, many choose to provide formula milk as a substitute for breast milk due to various factors. It can be concluded that mothers have been carried away by the influence of the times and do not pay much attention to the provisions of Islam that breastfeeding is the responsibility of mothers to their children after giving birth.